Efeitos prototípicos da intercalação de Cláusulas Hipotáticas Circunstanciais Temporais no Espanhol mexicano oral - Cavalcante, Sávio André de Souza (2020)
Intercalation is sparsely defined in linguistics research. Considering the complexity of the phenomenon, this thesis analyzes the intercalation of Temporal Circumstantial Hypotatic Clauses in oral Mexican Spanish, under the assumptions of the Usage-based Functional Linguistics. Therefore, (i) we identified criteria for its characterization; (ii) we map its loci; (iii) we proposed a scalar configuration, prototypically oriented; (iv) we analyze its uses, observing syntactic-semantic-discursive features; and (v) we correlate the results with iconicity and markedness (GIVÓN, 1995, 2001a). We argue which the intercalation can be analyzed as a gradient phenomenon, consisting of scalarly hierarchical substructures, which exhibit prototypical effects. The Methodology involved the collection, coding and analysis of Temporal Clauses interposed in 54 interviews of the Corpus Sociolingüístico de la Ciudad de México (CSCM). The results of the 514 localized data point to a preference for nonprototypical intercalation (449/87.3%), revealed in the following types, among which the first two were considered more distant from the intercalation prototype: a) Discursive marker (∆) Temporal (∆) Nuclear Clause, b) Coordinated Connector (∆) Temporal (∆) Coordinated Clause, c) Nuclear Clause (∆) Temporal (∆) Discourse Marker, d) Topic (∆) Temporal (∆) Nuclear Clause, e) Nuclear Clause (∆) Temporal (∆) Anti-theme, f) Adjunct adverbial (∆) Temporal (∆) Nuclear Clause and g) Subordinate connector (∆) Temporal (∆) Subordinate Clause. This first major category presented the following traces: (i) regarding the position and extension: pre-verbal (437/97.3%), short distance in relation to the verb (298/66.4%), short distance from the left margin (331/73.7 %), long distance from the right margin (304/67.7%), long extension (177/39.4%); (ii) regarding its formal presentation and its verbs: developed with cuando (339/75.5%), time/mode sharing with the nuclear verb (321/71.5%); (iii) regarding the subject: high topical accessibility (206/45.9%), high topical persistence (123/27.4%) and non-persistence (118/26.3%), co-referential (204/45.4%) and non-coreferential to the nuclear (231/51.4%), first person (231/51.4%) and third person (195/43.4%), evoked (381/84.8%), elliptical (281/62.6%); (iv) regarding chronological and semantic relations: simultaneity (251/55.9%); time and motive (126/28.1%); condition, time and motive (118/26.3%) and prototypical time (106/23.6%). The prototypes were manifested in the following types, among which the latter was considered the most similar to the prototype: a) Subject (∆) Temporal (∆) Verb, b) Verb (∆) Temporal (∆) Adverbial adjunct, c) Nuclear Clause (∆) Temporal (∆) Nominal complement, d) Verb (∆) Temporal (∆) Indirect object, e) Verb (∆) Temporal (∆) Direct object and f) Periphrasis auxiliary verb (∆) Temporal (∆) Verb main periphrasis. In addition to low frequency of use (65/12.7%), its characteristics are: (i) regarding position and extension: pre-verbal (54/83.1%), short (30/46.2%) and contiguous distance (27/41.5%) in relation to the verb, short distance from the left margin (40/61.5%), long distance from the right margin (37/56.9%), medium extension (23/35.4%); (ii) regarding its formal presentation and its verbs: developed with cuando (51/78.4%), time/mode sharing with the nuclear verb (54/83.1%); (iii) as to the subject: high topical accessibility (49/75.4%), high topical persistence (27/41.5%), co-referential to nuclear (49/75.4%), first person (38/58.4%), evoked (61/93.8%), elliptical (52/80%); (iv) regarding chronological and semantic relations: simultaneity (41/63.1%); time, condition and motive (21/32.3%) and prototypical time (16/24.6%). We perceive which the structural complexity of the interposed Temporals is compensated by mechanisms which tend to reduce or soften the codification efforts, corroborating iconicity, markedness (GIVÓN, 1995, 2001a) and expressiveness (DUBOIS; VOTRE, 2012). Its hybrid behavior, even within the same group, reveals a complex and heterogeneous mechanism for articulating clauses, attesting the feasibility of analyzing and segmenting its various types.